Model predictive control of bidirectional AC-DC converter for energy storage system - Akter P.; Mekhilef S.; Tan N.M.L.; Akagi H. (Korean Institute of Electrical Engineers, 2023)
Controllers; Cost functions; Dynamic response; Electric energy storage; Electric power distribution; Electric power factor; Electric rectifiers; Energy storage; HVDC power transmission; MATLAB; Model predictive control; Power converters; Predictive control systems; Reactive power; Renewable energy resources; Switching functions; Ac-dc converters; Bidirectional power flow; Efficiency comparisons; Energy storage systems; Experimental prototype; Renewable energy source; Three-phase ac voltage; Unity power factor; Rectifying circuits